2014
DOI: 10.5194/acp-14-8369-2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term halocarbon observations from a coastal and an inland site in Sabah, Malaysian Borneo

Abstract: Abstract. Short-lived halocarbons are believed to have important sources in the tropics, where rapid vertical transport could provide a significant source to the stratosphere. In this study, quasi-continuous measurements of short-lived halocarbons are reported for two tropical sites in Sabah (Malaysian Borneo), one coastal and one inland (rainforest). We present the observations for C 2 Cl 4 , CHBr 3 , CH 2 Br * 2 (actually ∼ 80 % CH 2 Br 2 and ∼ 20 % CHBrCl 2 ) and CH 3 I from

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…The TWP, particularly during boreal winter, is a region of active convection and one of the most important pathways for compounds with short tropospheric lifetimes to reach the stratosphere (Aschmann et al, 2009;Bergman et al, 2012;Levine et al, 2007;Schofield et al, 2011). Consequently, the TWP and nearby Southeast Asia have been regions where a number of ground and ship-based campaigns have been conducted to study oceanic emissions of VSLS (Brinckmann et al, 2012;Mohd Nadzir et al, 2014;Robinson et al, 2014). Additionally, aircraft campaigns observed mixing ratios of VSLS in Southeast Asia that were slightly elevated with respect to measurements collected in the rest of the tropics (Sala et al, 2014;Wisher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The TWP, particularly during boreal winter, is a region of active convection and one of the most important pathways for compounds with short tropospheric lifetimes to reach the stratosphere (Aschmann et al, 2009;Bergman et al, 2012;Levine et al, 2007;Schofield et al, 2011). Consequently, the TWP and nearby Southeast Asia have been regions where a number of ground and ship-based campaigns have been conducted to study oceanic emissions of VSLS (Brinckmann et al, 2012;Mohd Nadzir et al, 2014;Robinson et al, 2014). Additionally, aircraft campaigns observed mixing ratios of VSLS in Southeast Asia that were slightly elevated with respect to measurements collected in the rest of the tropics (Sala et al, 2014;Wisher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tropical regions are highly important for atmospheric research, and whilst long-term atmospheric observations exist (Robinson et al, 2014;Pyle et al, 2011), there are fewer measurements than in the mid and high latitudes. The Bachok Marine Research Station (lat 6.00892, long.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows that there are some differences in the absolute mixing ratio observed at the two sites. Instrument performance is generally good for this compound (Gostlow et al, 2010) although Robinson et al (2014) have raised the possibility of calibration uncertainty leading to part of this difference. In this study we focus on the variations observed concurrently at both locations, and hence the absolute mixing ratios are of lesser importance.…”
Section: Observationsmentioning
confidence: 99%
“…The number of 3 h periods, n, contributing to each composite is noted above each panel. A mixing ratio greater than 2.4 ppt was observed in eleven 3 h windows; these periods are not accounted for in the figure. this gap, we have used University of Cambridge µ-Dirac instruments (Gostlow et al, 2010) to measure a suite of halocarbons at a number of sites in the region (see Pyle et al, 2011;Robinson et al, 2014). Here we focus on C 2 Cl 4 observations collected at two locations in Sabah, Malaysian Borneo.…”
Section: Observationsmentioning
confidence: 99%